Performance of Coal Gangue-Based Cemented Backfill Material Modified by Water-Reducing Agents - Yuxia Guo; Peng Wang; Guorui Feng; Tingye Qi; Guoyan Liu; Ang Ren (Advances in Materials Science and Engineering)
Coal gangue-based cemented backfill material (CGCBM) is developed for backfilling the goaf in coal mines. As fresh CGCBM slurry is generally transported into underground openings through a pipeline, and after hardening, it plays the role of supporting the overlying strata. The fluidity, stability, and mechanical (compressive strength) of CGCBM become the most important properties. Adding water-reducing agents (WRAs) is considered to improve the fluidity, stability, and mechanical properties of CGCBM, but there is a risk of increased bleeding. So, two types of WRA (naphthalene series (WRA1) and poly carboxylic acid (WRA2)) are used at different contents (1.0%-2% for WRA1, 0.2%–0.6% for WRA2) by mass of binder. Slump, slump flow, yield stress, and plastic viscosity test are used to evaluate the fluidity properties of CGCBM after adding WRA. Bleeding rate test is used to evaluate the stability of CGCBM after adding WRA. Compressive strength is the most important factor in measuring the mechanical properties. SEM and XRD tests are used to analyse the mechanism of strength change. Results show that the slump, slump flow, and plastic viscosity increase after adding WRA, which reduces the yield stress and improves the fluidity. The bleeding rate increases with the increase of WRA content, leading to a decrease in stability. Adding WRA increases the compressive strength, and it increases first and then decreases with the increase of the content at the later stage. Considering the effects of WRA on the fluidity, stability, and compressive strength properties of CGCBM, the reasonable content of WRA1 and WRA2 is 1.5% and 0.4%, respectively. The research results provide guidance for the design and preparation of CGCBM with favourable performance in practical production.